Cyberbully - Osment, Emily; Panabaker, Kay, 1990-; Rath, Meaghan, 1986-; Rowan, Kelly; Muse Entertainment (Firm); ABC Family (Television network); Gaiam Americas, Inc. (Louisville, CO : Gaiam Americas, Inc., 2012)
A seventeen-year-old girl receives a computer for her birthday and soon finds herself the victim of betrayal and bullying while on a social website. When she is pushed to the breaking point, her mother takes on the school system and the legislature to make sure no other teen has to experience the same treatment.
Videodisc release of the 2011 television production.
Release date: Feb. 7, 2012.
Director of photography, Pierre Gill ; editor, Simon Webb ; music, James Gelfand.
Emily Osment, Kay Panabaker, Meaghan Rath, Kelly Rowan.
Not rated.
DVD, widescreen, region 1; Dolby Digital 2.0.
Keywords: Teenage girls -- Drama; Online social networks -- Drama; Cyberbullying -- Drama; Made-for-TV movies; Video recordings for the hearing impaired